The study of customer satisfaction towards internet banking / Intan Norhawani Abu Bakar - Abu Bakar, Intan Norhawani (Faculty of Business and Management, 2011)
Internet banking is one of the most popular services utilized by the Malaysian retail banking customers in recent years. Despite its attractiveness, studies have shown that the quality of e-services is core an issue that influences customer’s satisfaction of Internet banking services worldwide. The objective of this study is to evaluate consumer satisfactions on Internet banking adoption in Malaysia. Results show that Internet banking users has influences by four predictors which is convenience, security and privacy, compatibility and services. The implications are discussed and recommendations are made in order to improve Internet banking service in Malaysia.